PENGARUH MOTIVASI, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KABUPATEN PARIGI MOUTONG - Rusadi, Hary (Katalogis, 2018)
This study aims to determine and analyze the influence of motivation, work discipline and organizational culture on official performance in Transportation Departement of Parigi Moutong. The selection of 47 respondents is using census technique. Method of analysis is multiple linear regressions. The result shows F-value equals to 24.008 on Î¬ = 0.05 or F-sig value <0.05 with F-significance equals to 0.000, which means that independent variabels simultaneously have positive but non-significant influence on the dependent variable. Partially, the result show that motivation has positive but non-significant influence on performance with sig-value of 0.199; work discipline has positive and significant influence on performance with sig value 0.001; organizational culture has positive and significant influence on performance with sig value of 0.005